(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In the context of information progress, new types of disease are spreading, the so-called non-chemical addictions, associated with a form of behavioral addiction. Computer addiction has already been diagnosed by scientists as a mental pathology of the user of information technology, subsequently overly uncontrolled operation of information devices, which ranges from mobile communications: phones, tablets, netbooks, laptops and computers. Computer addiction is a mental disorder accompanied by many other diseases, the cause of which is inactivity during Internet communication. In this regard, there was a need for collective efforts to understand the problems associated with real and virtual existence, rationally organize their healthy lifestyle, and prevent non-chemical diseases. Naturally traditional medicine used the technique of medical prevention through active reality and potential virtual existence in the form of heaven and hell. Thanks to the progress of science and technology, a person has managed to create a virtual world of information and has been able to use it as a negative weapon, as well as to satisfy his interests and ensure the well-being of his life. In this sense, the article aims to conduct a scientific and philosophical analysis of computer addiction as a mental pathology of a person.